Exchange rates volatility modelling - Rodrigues, Hristiyan-Alekzandar Krastanov (2020)
We investigate the empirical relevance of structural breaks in the unconditional variance of exchange rate returns for seven currency pairs vis-à-vis the US Dollar over the 2002 - 2018 period. We find evidence of structural breaks in the unconditional variance for five of the seven currencies under our scope with a high degree of persistence and variability in the parameter estimates of the GARCH (1,1) model across the various subsamples defined by the structural breaks. When analysing the time of occurrence of these breaks, we are able to associate a vast majority of them to relevant social, political and economic events occurring on both a regional and a global scale. Our research indicates that structural breaks are an empirically relevant feature of exchange rate volatility modelling and should be accounted for when performing volatility forecasts